PENETAPAN ELEMEN KUNCI PENGEMBANGAN AGROINDUSTRI PETERNAKAN DENGAN INTERPRETATIVE STRUCTURAL MODELING (ISM) - Mirah, Arie Dharmaputra (Universitas Sam Ratulangi, 2014)
Although the livestock sub-sector contributes significantly to the economic growth of North Sulawesi, but to date not include leading commodity in the agro-industry development. The problems to be studied in livestock development efforts is the absence of the establishment / implementation of appropriate strategies to be able to maximize the potentials that exist that allow livestock into a competitive industry. The study was conducted through the following steps: - Conducting searches of information sources that can give an idea of ​​the limitations, the principal research, development and problems in the sub-sector prternakan, regional understanding, understanding strategic management, then set formulations for the purpose of research towards implementation. - Conducting a survey of experts to examine and define the elements / sub-elements associated with the development strategy of the farm estate sector agro-industry. - Designing systems structuring with a review / determination of the development of key elements, with Interpretative Structural Modeling (ISM). Based on the results of expert assessments set by 4 elements and 12 sub-elements that have a strong interaction with the development of animal husbandry in North Sulawesi. Into elements have analyzed the level of interaction with the ISM-VAXO technique. The first stage is to study contextual relationships in matrix form SSIM-VAXO. This method has been able to classify all of elements into four quadrants based on the value Drive Power and DependenceI and in a hierarchical structure based on rank and level, which then informs the development of animal husbandry sub key elements namely: Provision of sub-elements of human resources with knowledge and skills appropriate breeding (7) and sub-elements Improved managerial skills training programs (8). Keywords: livestock, strategy, ISM